2020
DOI: 10.1088/1748-9326/ab6616
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal tropospheric cooling in Northeast China associated with cropland expansion

Abstract: Large-scale agricultural expansion can influence near-surface climate by altering surface energy fluxes, water, and albedo. It is less clear whether such effects extend through the full troposphere and how such effects vary in time. Here we use a novel dataset documenting the massive land use and land cover change due to agricultural expansion in Northeast China from 1982 to 2010 to assess how such expansion has influenced climate over the full troposphere. Confronting our land classification and climate data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…This may be because irrigation is intense in the southern BTHR, and this has a significant cooling effect on the daily maximum temperature, which partially offsets the effect of urbanization [40]. Clearly, the cooling effects of cropland cannot be ignored [41]. At most stations, the daily minimum temperature and the indices of frequency of extreme cold weather events significantly increased and decreased, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because irrigation is intense in the southern BTHR, and this has a significant cooling effect on the daily maximum temperature, which partially offsets the effect of urbanization [40]. Clearly, the cooling effects of cropland cannot be ignored [41]. At most stations, the daily minimum temperature and the indices of frequency of extreme cold weather events significantly increased and decreased, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pettorelli et al [86] highlighted that, NDVI in ecological studies has recently rapidly increased and its possible key role in future research of environmental change in an ecosystem context allows the better predictions of the effect of global warming, biodiversity reduction or habitat degradation. In fact, He et al [34] and Wang et al [87] found a positive correlation between the temperature and NDVI early and late in the growing season and a weak correlation in the mid-growing season in Kansas during the 1989-1997 period. Southern areas surrounding stations such as Kissidougou, Macenta and N'zerekore have stronger NDVI values, and the surface temperatures of these areas are less sensitive to the seasonal warming during March-April-May (MAM) compared to the rest of the country.…”
Section: Trend Estimation By Mk and Sq-mkmentioning
confidence: 99%
“…Some research works have analyzed these LCCs and their impacts on the climate, such as that of Mahmood et al [33], who studied the impacts of notable types of land cover changes, including agriculture, deforestation and afforestation, desertification and urbanization on the climate. In addition, the agricultural expansion influence on the climate over the full troposphere in Northeast China from 1982 to 2010 was studied by He et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, India monsoon precipitation is altered in response to changes in the surface fluxes from urbanization and, to some extent, the change of prevalent mixed forest into deciduous needle/leaf forest in Kerala [23]. As another example, there has been documentation of tropospheric cooling in northeast Asia due to cropland expansion [24].…”
Section: Convergent Definitionsmentioning
confidence: 99%